Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1021/es960709z
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Environmental Variables and Supercritical Fluid Extraction Parameters on the Extractability of Pesticide Residues from Soils Using a Multivariate Optimization Scheme

Abstract: A multivariate optimization scheme (MOS) was used to investigate the effects of environmental variables and supercritical fluid extraction (SFE) parameters on the extractability of pesticide residues from soil samples. MOS is a highly efficient technique for studying a large number of variables and identifying optimal extraction conditions. MOS offered the opportunity to systematically and simultaneously examine the interaction and effect profiles among important soil variables and extraction parameters. Pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…It is confirmed that the extractability of pesticide residues from soil samples is strongly affected by environmental variables and SFE parameters. To further verify the most significant variables, a multivariate optimization scheme (MOS) was employed by Zhou et al [120] to investigate the effects of those parameters on the extractability of several pesticides from soil. Later, they concluded that the extractability of pesticides residues from soil was also dependent on the particular pesticide examined and on the nature of residues.…”
Section: Hazardous Substances Extraction From Soil and Sedimentmentioning
confidence: 99%
“…It is confirmed that the extractability of pesticide residues from soil samples is strongly affected by environmental variables and SFE parameters. To further verify the most significant variables, a multivariate optimization scheme (MOS) was employed by Zhou et al [120] to investigate the effects of those parameters on the extractability of several pesticides from soil. Later, they concluded that the extractability of pesticides residues from soil was also dependent on the particular pesticide examined and on the nature of residues.…”
Section: Hazardous Substances Extraction From Soil and Sedimentmentioning
confidence: 99%
“…Experimental designs are well suited to optimisation of experimental conditions which are known to influence the final results [21,23,31,32]. Accordingly, a full factorial was designed for the determination of the significant factors (humidity, solvent type, and sterilisation method) affecting the analytical system under study.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…Many procedures have been proposed for the extraction of organic contaminants from soil, including accelerated solvent extraction [19,20,21,22], supercritical-fluid extraction [21,22,23], and microwave-assisted extraction [24] which, in addition to increased analytical speed, lessen the cost per sample by reducing solvent consumption. However, they usually require sophisticated equipment not always available in modest laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…R e c e n t ly, a mu l t iva ri ate optimization scheme has been applied to the SFE of pesticide residues (atrazine, diuron and bensulfuron-methyl) from soils, using a quadratic model and a central composite design, and considering two groups of independent variables (soil environmental variables and SFE parameters) [55]. The analyte residence time in the soil was the most significant env i ronmental fa c t o r. Th e n , for age d samples (12 months), the soil organic matter and clay minerals content had a negative effect on the recoveries due to stronger analyte-matrix interactions (especially for bensulfuron-methyl).…”
Section: Soils and Sedimentsmentioning
confidence: 99%